Entrepreneurialism and society : consequences and meanings - Eberhart, Robert N.,; Lounsbury, Michael,; Aldrich, Howard, (Research in the sociology of organizations ;, 2022)
The second of two volumes bringing together researchers from an array of disciplines including sociology, organization theory, strategy, and organizational behaviour, Entrepreneurialism and Society: Consequences and Meanings addresses the question of how entrepreneurship has transformed from an organizing activity into an ideology that is changing society. The authors investigate how the transformed meanings of entrepreneurship are causal in new social phenomenon such as organizational misconduct and driving inequality, but also how it may offer a promise to resolve those issues. Examining into the role of organizations in society, Entrepreneurialism and Society invigorates academic research by developing new perspectives on how entrepreneurs and their organizations shape our social world.